Pelatihan Pemanfaatan Fitur LMS Berbasis Moodle dalam Upaya Peningkatan Pengalaman Pembelajaran Bauran untuk Pengajar di Sekolah Binekas - Nasution, Surya Michrandi; Septiawan, Reza Rendian; Latuconsina, Roswan (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
The pandemic era brought extreme changes in every sector, including in the learning process which has changed from offline to online system. Even though the pandemic era is over, the habits of online learning are still happening in the academic sector. In this pasca pandemic era, online learning is not only still being done in higher education, but also in primary or secondary school. Sekolah Binekas is a primary school located in southern Bandung that has begun to implement hybrid learning. This school has already implemented the Learning Management System (LMS) platform, but its use is not optimal since several teachers are unfamiliar with their new system. Through these community services, the teacher may maximize the LMS’s features that are able to make it easy to dot the academic and administration activity from Sekolah Binekas.